2017
DOI: 10.1080/10426914.2017.1279306
|View full text |Cite
|
Sign up to set email alerts
|

Surface integrity of Mg-based nanocomposite produced by Abrasive Water Jet Machining (AWJM)

Abstract: This paper investigates the influence of jet traverse speed on the surface integrity of 0.66 wt% Al2O3 nanoparticle reinforced metal matrix composite (MMC) generated by Abrasive Water Jet Machining(AWJM). Surface morphology, surface topography and surface roughness (SR) of the AWJ surface was analyzed. The machined surfaces of the nanocomposites were examined by laser confocal microscope and field emission scanning electron microscope (FESEM). Microhardness and elasticity modulus measurement by nanoindentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Hashish’s 11 work reported that selection of machining parameters is highly important in AWJM to avoid formation of burrs, cracks, and delamination and for good surface quality, as well as kerf behavior. A vast amount of work has investigated the performance of AWJM on various materials, notably Mardi et al, 12 which investigated the effect of AWJM on the surface quality of Mg-based nano composites. Karakurt et al 13 studied the performance of AWJM on cutting the granites; experimental results proved the effectiveness of machining on kerf angle.…”
Section: Introductionmentioning
confidence: 99%
“…Hashish’s 11 work reported that selection of machining parameters is highly important in AWJM to avoid formation of burrs, cracks, and delamination and for good surface quality, as well as kerf behavior. A vast amount of work has investigated the performance of AWJM on various materials, notably Mardi et al, 12 which investigated the effect of AWJM on the surface quality of Mg-based nano composites. Karakurt et al 13 studied the performance of AWJM on cutting the granites; experimental results proved the effectiveness of machining on kerf angle.…”
Section: Introductionmentioning
confidence: 99%
“…However, magnesium-based materials suffer from low corrosion resistance, low ductility and modulus of elasticity, low abrasion resistance and poor creep resistance which limits their use in structural applications. These limitations can be circumvented by the development of new magnesium-based composites and nanocomposites [1,[3][4][5]. Mg-based alloys and composites are well-addressed by many researchers for improving the mechanical properties along with ductility.…”
Section: Introductionmentioning
confidence: 99%
“…The only drawback of AWJM is lesser efficiency in creating highquality surfaces which can be expected from the other two methods. Bimla Mardi et al [29] investigated the surface integrity of Mg-based nanocomposites generated by AWJ. Feasibility of AWJ in machining Mg-based nanocomposites was reported.…”
Section: Overview Of Nontraditional Machining Of Mg-based Materialsmentioning
confidence: 99%